Genre based learning model integrated literacy activities and character strengthening - Atmazaki, Atmazaki; Ramadhan, Syahrul; Indriyani, Vivi (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2023)
Genre based learning or Text-based Instruction is a learning approach used in Indonesian language learning since 2013 until now. However, learning will be more engaging if the learning process is constantly adapted to students' needs and innovations. This study aimed at building a Genre-based Learning paradigm that incorporates literacy activities and character development. The guidelines of the National Literacy Movement and Strengthening Character Education in secondary schools prompted this action. Based on this, the two things are integrated in learning to help teachers implement literacy and strengthen character education in the learning process. This research employed Plomp's Development model (Preliminary Research, Prototyping Phase & Assessment Phase). In the Assessment Phase, researchers tested products that had been developed to determine the practicality and effectiveness of learning Indonesian using the developed model. The research instruments are in the form of questionnaires, observation sheets and tests. The research subjects were students of one of the high schools in the city of Padang. The results demonstrated that the Genre-based Learning model, which integrates literacy activities with character development, is useful and time-efficient for language learning. Additionally, this concept is applicable for enhancing student learning activities. This learning strategy can be utilized as an option to combine literacy activities and character development into secondary school Indonesian language instruction.